Making light of darkness: crime and justice in LEGO Star Wars: the Skywalker Saga - Atkinson, Colin (Video games, crime and control, 2024)
Contributing to the developing area of popular criminology this chapter conducts an analysis of the 2022 video game LEGO Star Wars: The Skywalker Saga. Focusing upon three in-game case-study sites and utilizing critical discourse analysis, this chapter explores the extent to which LEGO Star Wars: The Skywalker Saga uses humor in both narrative and gameplay to portray issues of crime and justice, and the potential effects of these representations on a diverse demographic of players. The chapter posits that the practices and politics of crime and justice are not entirely eradicated from the game, but are instead presented and played “for laughs.” This comedic treatment works to censor, sanitize, and sometimes erase these issues; compounded by the video game’s playful aesthetic. The chapter concludes by tracing the limits of LEGO’s postmodern sensibilities and the subversive comedy of LEGO Star Wars: The Skywalker Saga as it seeks to “make light of darkness.”